Implementasi Toleransi Beragama di Pondok Pesantren (Studi Kasus di Pondok Pesantren Universal Bandung) - Wiantamiharja, Irfan Setia Permana (Hanifiya: Jurnal Studi Agama-Agama, 2019)
The symptoms of religious intolerance in Indonesia began to undermine diversity in Indonesia. The most influential factor in encouraging the occurrence of these symptoms is education. In this case, education that is Islamic in mind is a pesantren. Pesantren is an educational institution that has its own perspective and style of thinking about tolerance. This study aims to determine the constructs of thought and the implementation of religious tolerance implemented in education and activities carried out at Universal Islamic Boarding Schools.Â This study uses descriptive qualitative research methods using observation, interview, and documentation techniques. The results of the study show that: The construction of thoughts built on religious tolerance is categorized as inclusive thoughts and attitudes in religion, namely thoughts that believe in the existence of truth in other religious beliefs. The foundation of the thought construction is tasamuh, which is a moderate style of Islamic understanding. The concept of religious tolerance is implemented in the policies of Universal Islamic boarding schools through a curriculum of educational activities that reflects education with a multiculturalism-pluralism pattern. This education includes conflict resolution education, Human Rights (HAM), pesantren education for peace. Regarding activities that reflect multiculturalism-pluralism education, namely muhadlarah, pesantren for peace seminars, and cross-cultural discussions with various universities without favoritism.